The Methodological Prescriptions of the "Appendix to the Transcendental Dialectic" of Kant's Critique of Pure Reason and the Foundations of Improper Science - Arias-Albisu, Martín (Studia Kantiana, 2017)
In the Preface to his Metaphysical Foundations of Natural Science, Kant holds that empirical disciplines, such as -at least- chemistry, are improper natural sciences. What he has primarily in mind is the phlogistic chemistry mainly developed by Georg Stahl. Contrary to mathematical physics, phlogistic chemistry is not a proper natural science because it lacks a metaphysical pure part and mathematics cannot be adequately applied to its domain. The aim of this article is to show that the scientific character of improper sciences, such as -at least- phlogistic chemistry, depends on the application of two methodological prescriptions demanded by the regulative function of theoretical reason. These prescriptions are presented by Kant in the Appendix to the Transcendental Dialectic of his Critique of Pure Reason. The first prescription requires the use of certain ideas of reason in empirical scientific laws. The second one consists in a demand of systematicity for those laws.